Developing, Using, and Interacting in the Flipped Learning Movement: Gaps among Subject Areas - Chen, Hsin-liang; Summers, Kevin L. (International Review of Research in Open and Distributed Learning, 2015)
The purpose of this paper is to investigate the current video collection of an open-access video website (TED-Ed). The research questions focus on its content as evidence of development, its viewership as evidence of use, and flipping as evidence of interaction in informal learning. In late September 2013, 686 video lessons were posted on the TED-Ed website that spanned 12 academic subject categories and 60 academic subject subcategories, as labeled and sorted on the TED-Ed website itself. The findings of the analysis of the TED-Ed video collection indicate several gaps in the humanities, social science, and natural science academic areas in terms of the number of video lessons and viewership. Despite the gaps in the numbers of video lessons and the viewership across those three academic areas, the areas have very similar averages of daily flipped lessons. The future research agenda should focus on the motivation of viewers to create flipped lessons as evidence of learning in an open learning environment.